2017
DOI: 10.22161/ijeab/2.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Composite Endomycorrhizal Inoculum on Olive Cuttings under the Greenhouse Conditions

Abstract: Abstract-This study was carried out in a nursery to evaluate the impact of mycorrhizal fungi on the cutting's root growth, and root colonization of a Moroccan olive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In comparison, spores' number/ 100 g of soil was of 697 spores/100 g soil recorded in site 1 of the second station greater than that of site 2 in the order of 169 spores/100 g soil with a dominance of the genus Dentiscutata nigra (32.13%) and Acaulospora denticulata (14.77%) (Figure 7). These two species were more prevalent than Glomus etunicatum (16.26%), Acaulospora gedanensis (10.52%) or Glomus macrocarpum and much more represented in the AMF community structure in southern area (Sellal et al, 2017). Regarding our findings about the number of spores extracted from the soil of argan trees, they seem to be lower than those cited by El Maati et al Moreover, it is known that the same fungus can colonise many plant species.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…In comparison, spores' number/ 100 g of soil was of 697 spores/100 g soil recorded in site 1 of the second station greater than that of site 2 in the order of 169 spores/100 g soil with a dominance of the genus Dentiscutata nigra (32.13%) and Acaulospora denticulata (14.77%) (Figure 7). These two species were more prevalent than Glomus etunicatum (16.26%), Acaulospora gedanensis (10.52%) or Glomus macrocarpum and much more represented in the AMF community structure in southern area (Sellal et al, 2017). Regarding our findings about the number of spores extracted from the soil of argan trees, they seem to be lower than those cited by El Maati et al Moreover, it is known that the same fungus can colonise many plant species.…”
Section: Resultscontrasting
confidence: 76%
“…At the same time, our assessment of the species' richness revealed some differences amongst the studied sites and stations. This variation has also marked the investigated sites of southern Morocco (Sellal et al, 2017;2021). A similar trend was observed for the number of spores in a 100 g soil; thereby, the highest spore density (585 spores/100 g soil) was related to site 4 of the first station followed by 518 spores/100 g soil, 204 spores/100 g soil, 201 spores/100 g soil, 154 spores/100 g soil, 101 spores/100 g soil, and 78 spores/100 g soil, detected respectively in sites 2, 5,7, 1,6 and 3.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…increased young olive plant growth and nutrient uptake in three olive genotypes. Furthermore, a mycorrhizal consortium of Glomus, Acaulospora, Gigaspora, Entrophospora, and Scutellospora species, increased the Na, Ca, and P concentrations in nutrient contents of 'Haouzia' olive cultivars under sandy loam soil conditions [32] and it was responsible for young olive plant-growth enhancement [12,32,33].…”
Section: Beneficial Microorganisms and Olive Tree's Growth Physiologmentioning
confidence: 99%
“…All of these types of plants are hosts of AMF. Several other studies related to the application of AMF in the manufacture of cuttings have been carried out on bougainvillea [15], olive [16], and andalas plant species which are endemic to West Sumatra [17]. The results of pre-study observations showed that in the rhizosphere of L. garciae, which grows naturally in the Green Open Space of the Faculty of Forestry Universitas Tanjungpura, an indigenous AMF population was found.…”
Section: Introductionmentioning
confidence: 99%